The Novel "Anak Rantau" by A. Fuadi as an Idea for Creating Illustrations - Aldiansyah, Muhammad; Fitryona, Nessya (V-art: Journal of Fine Art, 2023)
This article discusses illustrations from the novel "Anak Rantau" by A. Fuadi which is intended as a solution and to minimize the problem of teenagers' reading interest (literacy) and moral crisis using illustration images that are able to motivate teenagers to start reading. By presenting illustrations from the novel "Anak Rantau" by A. Fuadi, teenagers will be interested in understanding the contents of the novel so that the resulting output is moral in accordance with the ethical values taught by the novel. The type of illustration used is digital illustration, as a form of development of digital-based illustration techniques in this era of globalization. The technique used is a manual combination technique which is executed with the help of the Medibang application to digitize it. Pen, waercolour, an oil pastel is a type of pen used for sketching, coloring and final finishing which will be poured on digital paper measuring 40 x 60cm. Based on this discussion, it can be concluded that this work is in the form of illustration as an alternative solution that exists through an approach method with illustration work as a trigger to improve the quality of reading and ends with improving morals in teenagers.